Cardiac resynchronisation therapy and myocardial metabolism: acute and chronic effects in heart failure - Green, PG (2021)
Since its development in the 1990s, cardiac resynchronisation therapy has evolved to occupy a key position in the management of heart failure with a reduced ejection fraction and broadened QRS duration, inducing both acute haemodynamic improvements as well as chronic reverse remodelling. However, approximately 30% of patients appear to not respond to CRT. Whilst factors such as heart failure aetiology and patient comorbidity, e.g. diabetes mellitus, have been shown to correlate with poor response, the mechanisms responsible for this and strategies to improve response have in large part remained elusive. Meanwhile, changes in myocardial metabolic substrate usage and flux are increasingly thought to play a causative role in heart failure. Given the changes in cardiac efficiency and regional substrate uptake which are induced by CRT, this raises the intriguing possibility that changes in myocardial metabolism may influence reverse remodelling. This thesis aims to therefore further investigate the links between CRT and myocardial metabolism.